Optimized Packings with Applications - Fasano, Giorgio; Pintér, János D. (Springer Optimization and Its Applications, 2015)
This volume presents a selection of case studies that address a substantial range of optimized object packings (OOP) and their applications. The contributing authors are well-recognized researchers and practitioners. The mathematical modelling and numerical solution aspects of each application case study are presented in sufficient detail. A broad range of OOP problems are discussed: these include various specific and non-standard container loading and object packing problems, as well as the stowing of hazardous and other materials on container ships, data centre resource management, automotive engineering design, space station logistic support, cutting and packing problems with placement constraints, the optimal design of LED street lighting, robust sensor deployment strategies, spatial scheduling problems, and graph coloring models and metaheuristics for packing applications. Novel points of view related to model development and to computational nonlinear, global, mixed integer optimization and heuristic strategies are also discussed. Optimized Packings with Applications will benefit researchers and practitioners working on a broad range of topical engineering and operations research applications. Academics, graduate and post-graduate students in the fields of engineering, applied mathematics, operations research and optimization will also find the book useful, since it discusses a range of advanced model development and solution techniques and tools in the context of real-world applications and new challenges.